The Impact OF Behavioral Economics on the Purchasing Behaviors of Individuals in Some Arab Countries An inductive systematic review of some studies in this field (مجلة جامعة سرت للعلوم الانسانية, 2023)
This study aimed to review the literature related to the impact of behavioral economics on the purchasing behaviors of individuals, in some Arab countries. To achieve the desired goals, the 'PRISMA' methodology was relied upon in qualitative research, by examining scientific theses and related economic research. The number of studies that were examined and their results analyzed was (20) studies. The current study concluded that there is a positive relationship between the application of behavioral economics tools, and the purchasing behaviors of individuals, so that the use of behavioral economics tools influences the purchasing behaviors of individuals -when choosing among the available alternatives- and directs them towards positive behavior. The current study made several recommendations, including encouraging economic researchers to conduct more systematic reviews, and research related to consumer purchasing behavior. As well as studying the factors influencing consumer motives, and how do they affect economic decision-making, to serve the objectives of public policies and achieve economic development. In addition to educating the owners of commercial establishments about the importance of behavioral economics, in directing the behavior of their customers, in a way that serves their interest. Finally, it is necessary to pay attention to spreading awareness about behavioral economics, to help form more rational economic decisions, and reduce irrational decisions.
Keywords: behavioral economics; behavior of individuals; Economic Anthropology; consumer awareness